NANOSTRUCTURED MATERIALS FOR NEXT GENERATION LITHIUM-SULFUR RECHARGEABLE BATTERIES - Baikalov, Nurzhan (Nazarbayev University School of Engineering and Digital Sciences, 2023)
Lithium-sulfur (Li-S) batteries have become increasingly popular as a viable energy storage solution in recent years, providing an affordable replacement to lithium-ion batteries. Li-S batteries have several inherent benefits over LIBs, including a high specific capacity due to elemental sulfur (S8), that when combined with a lithium anode theoretically yields high gravimetric energy densities nearly ten times greater than lithium-ion batteries. However, some issues must be addressed before Li-S batteries can be commercialized, such as low sulfur loading, limited sulfur utilization, and the shuttle effect, all of which contribute to poor cycling stability, capacity loss, loss of active material, lithium anode degradation, and severe self-discharge. The research presents innovative advancements in modifying separators and cathode materials for Li-S batteries. Comparative analysis among nickel, cobalt, and iron revealed that Ni@NGC modification enhances cycle performance and reaction kinetics during lithium polysulfide conversion. Among different modifications, Ni@NGC stands out in various electrochemical aspects, demonstrating stable cyclability and low polarization. Post-cycling morphology analysis reveals a homogenous coating of sulfur compounds on the outer layer of current collectors and separators with Ni@NGC, explaining positive results electrochemical behavior of Li-S battery. Studies highlighted the substantial influence of metal weight percentage in Ni@NGC separator modifications on reaction kinetics and electrochemical characteristics, with 9% exhibiting the optimal ratio for nickel loading to material surface area. Electrochemical performance of separators with 9 wt% Ni loading is improved by capacity retention and reduced polarization. Amongst the separator modifications, the Ni@NGC_9 composite ideally balances the ratio of surface area to Ni content, improving Li-S cell reaction kinetics and cycle performance. After 200 cycles, even with 4.0 mg cm–2 sulfur loading, Ni@NGC_9-modified separator batteries maintain 77% capacity at 0.5 C. A novel cathode current collector, Ni/NiO@CNF, was proposed to expedite sulfur redox kinetics and mitigate the shuttle effect by leveraging the catalytic properties of Ni nanoparticles and the immobilization effect of NiO nanoparticles.
Keywords: Lithium-Sulfur Batteries; Nanostructured Materials; Modified Separators for Lithium-Sulfur Batteries; type of access: restricted